2011
DOI: 10.1017/s1368980011001765
|View full text |Cite
|
Sign up to set email alerts
|

Visual acuity in fish consumers of the Brazilian Amazon: risks and benefits from local diet

Abstract: Objective: To examine the associations between near and distant visual acuity and biomarkers of Hg, Pb, n-3 fatty acids and Se from the local diet of fish-eating communities of the Tapajós River in the Brazilian Amazon. Design: Visuo-ocular health and biomarkers of Hg (hair, whole blood, plasma), Pb (whole blood), Se (whole blood and plasma) and n-3 fatty acids (plasma total phospholipids) were assessed in a cross-sectional study. Setting: Lower Tapajós River Basin (State of Pará, Brazil), May to July 2006. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 44 publications
1
14
0
2
Order By: Relevance
“…On the contrary, these findings are consistent with other results in this study population showing positive associations between Se status and motor performances and near visual acuity (Lemire et al, 2011;Fillion, 2011a) and a lower prevalence of agerelated cataracts among those with elevated Se (Lemire et al, 2010b).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the contrary, these findings are consistent with other results in this study population showing positive associations between Se status and motor performances and near visual acuity (Lemire et al, 2011;Fillion, 2011a) and a lower prevalence of agerelated cataracts among those with elevated Se (Lemire et al, 2010b).…”
Section: Discussionsupporting
confidence: 92%
“…It is not clear at which levels organic Se from food intake may become unsafe. Our data in the Lower Tapajós region shows no deleterious effect of Se, and even beneficial effects of high Se status on health (Lemire et al, 2010a,b;Lemire et al, 2011;Fillion, 2011a). Whether dietary Se is less toxic in Hg-exposed populations remains unanswered.…”
Section: Discussionmentioning
confidence: 67%
“…Ocular findings revealed that the presence of Hg and Pb might increase the risk for visual acuity in older persons. However, loss of visual acuity during ageing is also diet-related, and consumption of n-3 fatty acids and Se has positive effects on eyesight [25]. Similar seafood studies lack information about direct lead and cadmium effects on the sight organ.…”
Section: Metals and Sight Organmentioning
confidence: 99%
“…Alguns estudos têm avaliado as consequências da exposição ao mercú-rio sobre o funcionamento do sistema nervoso dessas populações ou populações que sofrem de exposição semelhante 27,28,29,30,31,32,33,34,35,36 . Outros estudos têm mostrado que populações expostas ao mercúrio pela ingestão de peixes e com índices de mercúrio abaixo dos preconizados pela OMS apresentam alterações neurológi-cas diversas 27,28,32,34,37,38 .…”
Section: Introductionunclassified